2004
DOI: 10.1080/00140130410081658718
|View full text |Cite
|
Sign up to set email alerts
|

A systems perspective of slip and fall accidents on icy and snowy surfaces

Abstract: Current research on slips and falls has mainly focused on floors and/or contaminated floors. Although icy and snowy surfaces near melting temperature are more slippery, more important still, slip and falls on icy and snowy surfaces involve not only outdoor workers, but also pedestrians and the general public; and occur in cold regions and in the winter season in many parts of the world. However, in comparison with the size of the problem, research work done so far in this area has been limited. The objective o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
48
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(53 citation statements)
references
References 71 publications
4
48
0
1
Order By: Relevance
“…In our opinion the results of the present study validate the comprehensive systems model of factors contributing to slip and fall accidents on icy surfaces presented by Gao and Abeysekera (2004).…”
Section: Criteria For a Slip-resistant Winter Shoesupporting
confidence: 85%
See 3 more Smart Citations
“…In our opinion the results of the present study validate the comprehensive systems model of factors contributing to slip and fall accidents on icy surfaces presented by Gao and Abeysekera (2004).…”
Section: Criteria For a Slip-resistant Winter Shoesupporting
confidence: 85%
“…Most previous research on slips and falls identified by the author mainly focuses on floors and/or contaminated floors. However icy and snowy surfaces near thawing temperature can be more slippery (Gao & Abeysekera 2004). The most slip resistant soling material on floors and lubricated floors may not provide sufficient slip resistance on ice (Gao et al 2004).…”
Section: The Need For a Slip-resistant Shoementioning
confidence: 99%
See 2 more Smart Citations
“…86 Responders to an SCA on an ice playing surface should consider foot traction devices and helmets for their own safety. 87,88 In contrast, SCA victims found immersed in a pool or contained body of water should be removed from the water before defibrillation. Any SCA victims lying on metal conducting surfaces (eg, bleachers) should be moved to a nonmetal surfaces or placed onto spine boards before defibrillation if that can be done quickly and without significant delays.…”
Section: Rainy Wet Ice and Metal Surfacesmentioning
confidence: 99%